The Smartsettle as An Innovative Solution For Debt Dispute Resolution: A Game Theory Approach Powered By Artificial Intellegence - Albert Fajar Yuga Yusdi Putra; Dewi; Meivina Jayanti; Lee Yong Hwa; Muhammad Elvio (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2026)
: In the face of increasingly complex debt disputes, traditional litigation often proves inefficient due to its high costs, protracted timelines, and emotional toll. Smartsettle, an AI-powered Online Dispute Resolution (ODR) platform that integrates game theory, offers a promising alternative. This research explores Smartsettle's potential to resolve debt disputes more effectively by analyzing how artificial intelligence, when combined with strategic decision-making frameworks like Nash Equilibrium and utility modeling, can optimize negotiations between creditors and debtors. Through a normative-juridical and comparative approach, the study examines the theoretical underpinnings of AI and game theory, the current legal framework of debt obligations in Indonesian civil law, and international case studies—particularly in Canada—where Smartsettle has been successfully implemented. Results indicate that Smartsettle facilitates faster, more transparent, and cost-effective settlements while preserving business relationships. This paper also analyzes legal integration challenges, such as regulatory gaps, public trust in AI, and infrastructure readiness in Indonesia. The study concludes with policy recommendations to support AI-based ODR platforms and enhance legal modernization. Overall, Smartsettle represents a viable and forward-thinking model for addressing civil disputes in the digital era.